Efeito do preenchimento do canal de acesso ao parafuso e da angulação de pilares protéticos na resistência à remoção por tração das restaurações implanto-suportadas cimentadas - Bezerra, Rose Tatiane Patriota Alves (2009)
Introduction. The reversibility of implant-supported fixed prostheses cemented materials depends on retentiveness and providing adequate opportunity to revert to routine or corrective maintenance. Objective. This study aimed to determine what effect different materials to fill the screw access channel and angle abutment has a retention of cemented implant-supported crowns. Material and methods. The specimens consisted of straight and angled abutments. The screw was secured with tape and polytetrafluoroethylene access channel abutment screw left unfilled, filled with gutta-percha, silicone or resin composite. Custom cast cylinders were cemented with Temp-Bond NE or zinc phosphate. The set was stored in 100% humidity at 37 ° for 24 hours. The tensile force was set at the speed 0.5 mm / min. Results. The retention between abutments and straight, according to the Student t test in both cementations, is statistically significant for all types of fill, except between bent and straight filled with gutta-percha and cemented with zinc phosphate. According to an analysis of variance ANOVA test, we assume the null hypothesis for the angled (α> 0.05) and reject the null hypothesis for the pillars straight (α <0.05) in both cementations . The Tukey test accused statistically significant difference between gutta-percha and unfilled cemented with Temp-Bond NE and gutta-percha between silicone and cemented with zinc phosphate. Conclusions. The upright pillars are significantly more retentive than bent. For cementing provisional abutments, whose retention is decreased, the election of gutta-percha as a filling material will be an ally in the cemented implant-supported prostheses. In the final cementation of both columns, the suggestion falls on the composite, due to their superior properties over other materials about the longevity, dimensional stability and sealing.